Understanding Tax Law, Taxes, Tax History, Tax Functions and Tax Type Classification - Ryan Fahri Rangkuti; Taufik Hidayat Batubara; Ahmad Asri Nasution; Darmawan Setia; Ikhwan Hakim (ISNU Sumatera Utara, 2024)
The branch of public law known as tax law regulates the relationship between the state as tax collector and the public as taxpayers. The purpose of this study is to provide a comprehensive explanation of the definition, fundamentals, history, function, and classification of taxes. Tax law is divided into formal tax law, which regulates how taxes are collected, and material tax law, which regulates the types of tax obligations. According to experts such as Rochmat Soemitro, R. Santoso Brotodihardjo, and PJA Adriani, taxes are mandatory contributions to the state to finance general expenditures for the welfare of the people, without direct compensation. Taxes have existed since prehistoric times and have developed in complexity in the modern era as a result of the industrial revolution 4.0 and the digitalization of the tax system. Indonesian taxes have undergone many changes from the era of kingdoms and colonialism to the tax reforms implemented in 1983. Taxes serve a budgetary function, which functions to regulate the economy, stabilize prices, and redistribute income. One can categorize taxes based on their characteristics, objectives, and collecting institutions. It is hoped that this study will provide a conceptual basis for improving the tax law system and increasing awareness of taxpayer law.